2013
DOI: 10.1039/c3sc00099k
|View full text |Cite
|
Sign up to set email alerts
|

N-Heterocyclic carbene (NHC) catalyzed chemoselective acylation of alcohols in the presence of amines with various acylating reagents

Abstract: This edge article reports the synthesis and full characterization including X-ray analysis of three different acylazolium ions. The reactivity of these acylazolium ions as acylating reagents of amines and alcohols is discussed. Whereas benzylamine slowly reacts with the acylazolium ions, benzyl alcohol acylation does not occur. However, upon activation of the alcohol with an N-heterocyclic carbene (NHC) as catalyst, efficient esterification is achieved. Importantly, benzylester formation is obtained in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 59 publications
3
59
0
Order By: Relevance
“…Yadav and co-workers reported the ring opening of epoxide by the Breslow intermediate 11 to provide the corresponding Aldol products [36]. Studer et al reported the preparation of acids by an oxidation of Breslow intermediates with molecular oxygen [3739]. The highly activated Breslow intermediate 11 formed by the addition of the NHC to the aldehydes, reacts with dioxygen to form the peroxy-species, which afforded the corresponding hydroxypropyl benzoate.…”
Section: Resultsmentioning
confidence: 99%
“…Yadav and co-workers reported the ring opening of epoxide by the Breslow intermediate 11 to provide the corresponding Aldol products [36]. Studer et al reported the preparation of acids by an oxidation of Breslow intermediates with molecular oxygen [3739]. The highly activated Breslow intermediate 11 formed by the addition of the NHC to the aldehydes, reacts with dioxygen to form the peroxy-species, which afforded the corresponding hydroxypropyl benzoate.…”
Section: Resultsmentioning
confidence: 99%
“…To qualitatively check for cooperativity we prepared acylazolium ion 12 as a subsystem and analyzed its reactivity as alcohol or amine acylation reagent . If acylation is attempted in the absence of any free NHC in THF at room temperature with benzylamine and benzyl alcohol (1.5 equiv.…”
Section: Considering Activation Energy To Describe Cooperativitymentioning
confidence: 99%
“…Recently, chemoselective O‐acylation of a hydroxy group in the presence of an amino group that included our zinc cluster catalysts was reported . In contrast, there are only few reported O‐selective acylations using activated esters, likely because their high reactivity causes a background reaction of the more reactive amino group without the assistance of a catalyst . In addition, catalytic transesterification of sterically congested tertiary alcohols, especially synthetically useful tert ‐butanol, has never been achieved.…”
Section: Initial Evaluation Of Catalysts[a]mentioning
confidence: 99%